Psycho-social Factors Correlated Health Care Behaviors in Diabetic and High Blood Pressure Patients at Risk of Cardiovascular Disease in the Area of Nakhon Sawan Province - Payakwichian, Gowit (Journal of Social Sciences and Humanities Research in Asia, 2021)
The purposes of the research were to investigate the relationship and to search for significant predictors of situational and psychosomatic characteristics related to health care attitudes and behaviors in people with diabetes and hypertension. The sample consisted of 400 people with diabetes and high blood pressure at risk of cardiovascular disease in Nakhon Sawan Province. This trial was collected from a stratified quota sampling. Data were collected with questionnaires tested for content validity, item discrimination, and confidence values, then analyzed by statistical correlation coefficients and multiple regressions. The results showed attitudes towards health behaviors demonstrated a statistically significant direct correlation with health behaviors (the correlation coefficient was .626, p<.01). Family health care support and perceived risk conditions had statistically significantly a positive association with health behaviors (the correlation coefficient was .431, p<.01 and .452, p<.01). Mental health, internal locus of control and locus of control provided a statistically significant direct correlation with health behaviors (the correlation coefficient was .267, p<.01 .350, p<.01 and .163, p<.01). In addition, when health care behavior scores were used for multiple regression analysis using situational factors, psychological traits and psychological states as predictors, able to predict in the overall group 31.8%. The order of important predictors was attitude towards health care behavior, perception of disease risk condition and internal locus of control. All of these have beta values of .46, .24 and .16, respectively. The results of this research can be used as practical recommendations to relevant agencies to improve the quality of life. It is also an extension of the foundation for research on health care behaviors in diabetic and hypertension patients who are at risk of heart disease and vascular disease in the future.